2018
DOI: 10.1093/jjco/hyy070
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of different lymph node staging systems in rectal adenocarcinoma with or without preoperative radiation therapy

Abstract: When assessed as a categorical variable, LNR was the most powerful method to predict survival for Stage II-III RC patients with limited TNLN. Rather, LODDS was the most accurate staging system regardless of the TNLN when LN status was modeled as continuous variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…LNR is defined as the ratio of NPLN relative to the NDLN. Recently, some scholars have reported that LNR has been shown to have a strong independent prognostic value in rectal and colon cancer (11, 12). These results were also shown in patients with lung, breast, and gastric cancer (1315).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LNR is defined as the ratio of NPLN relative to the NDLN. Recently, some scholars have reported that LNR has been shown to have a strong independent prognostic value in rectal and colon cancer (11, 12). These results were also shown in patients with lung, breast, and gastric cancer (1315).…”
Section: Introductionmentioning
confidence: 99%
“…However, some experts believe that when the NDLN is not sufficient, LNR cannot completely eliminate staging migration (18, 19). In addition, when LNR is an extreme value (LNR = 0 or 1), it does not accurately predict prognosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…A férfiak esetében a harmadik, míg nők esetében a második leggyakoribb daganattípust képezik [1]. Az elhalálozási arányokat tekintve a második helyen állnak, nemtől függetlenül [2,3]. Saját adataink alapján a rectum daganatok megjelenéséhez kötött átlagéletkor a férfiak és nők esetében egyaránt 66 év [4].…”
Section: Bevezetésunclassified
“…The LN ratio (LNR) is defined as the ratio of the number of PLNs to RLNs. Some researchers believe that the LNR has a stronger prognostic impact on patients with colon cancer[ 5 ], and that it is accurate for predicting the survival of patients with stage II-III rectal adenocarcinoma with limited RLNs[ 6 ]. Additionally, the LNR has shown great predictive value in other cancers, such as lung cancer[ 7 ] and gastric cancer[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the LNR has shown great predictive value in other cancers, such as lung cancer[ 7 ] and gastric cancer[ 8 ]. However, when the LNR is near 0 and 1, it cannot accurately evaluate the prognosis of patients with CRC[ 6 ].…”
Section: Introductionmentioning
confidence: 99%